Commodification Education at Darussolah Senior High School on Singojuruh, Banyuwangi- East Java Province - Mursidi, Agus; Salain, Putu Rumawan; Kumbara, AA. Ngr. Anom; Sukardja, Putu (International Journal for Educational and Vocational Studies, 2019)
Education in Indonesia has two gates for implementing education, namely under the auspices of the Ministry of National Education and Education under the auspices of the Ministry of Religion. In 2003 the existence of a law on regional autonomy opened up opportunities to establish public schools in Islamic boarding schools. This research was designed using qualitative research with emancipatory approaches, with the commodification theory. Data collection is done through observation, in-depth interviews, and documentation studies and literature studies. The analytical method used is qualitative descriptive. The results of the study show that commodification of education in Darussholah High School is very premature because (1) the facilities and infrastructures provided by Islamic boarding schools are very inadequate (2) School facilities and infrastructure Still need additional (3) curriculum still needs improvement and improvement because the school compiling education programs is closely related to the development of Islamic boarding schools with brilliant class programs that have the aim of improving the character of students through deepening religion and technology through general education.